2009
DOI: 10.2136/sssaj2007.0241
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Pedotransfer Functions for Estimating Soil Bulk Density Using Boosted Regression Trees

Abstract: Pedotransfer functions (PTFs) are used to estimate certain soil properties that are difficult and costly to measure from others more easily available. Bulk density is one important soil property. Although not requiring complex analysis, its measurement remains time consuming and is lacking in many soil surveys. For several decades, PTFs have been developed for predicting soil bulk density. Most of these PTFs are suited only for specific agro‐pedo‐climatic conditions, however, and can be applied only within a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 34 publications
2
86
1
2
Order By: Relevance
“…Pedotransfer functions are often applied instead to predict soil BD on the basis of SOC or soil organic matter content and soil texture data (Arrouays et al, 2012). It has been shown that most pedotransfer functions are suitable only for the agro-pedo-climatic conditions prevailing at the sites used to fit these functions (Martin et al, 2009). Under different conditions, they lead to substantial systematic errors (De Vos et al, 2005;Nanko et al, 2014;Vasiliniuc and Patriche, 2015).…”
mentioning
confidence: 99%
“…Pedotransfer functions are often applied instead to predict soil BD on the basis of SOC or soil organic matter content and soil texture data (Arrouays et al, 2012). It has been shown that most pedotransfer functions are suitable only for the agro-pedo-climatic conditions prevailing at the sites used to fit these functions (Martin et al, 2009). Under different conditions, they lead to substantial systematic errors (De Vos et al, 2005;Nanko et al, 2014;Vasiliniuc and Patriche, 2015).…”
mentioning
confidence: 99%
“…Recently, these principals have been applied to the prediction of both D b (Jalabert et al, 2010;Martin et al, 2009) and organic carbon stock (Wiesmeier et al, 2011;Grimm et al, 2008) at the point scale with considerable success. Methods commonly used to explicitly include landscape attributes in the modelling process are artificial neural networks (ANNs) (Keshavarzi et al, 2010) and random forests (RFs) (Prasad et al, 2006).…”
Section: K P Taalab Et Al: Modelling Soil Bulk Density At the Landmentioning
confidence: 99%
“…Many studies differentiate between topsoil and subsoil by depth (De Vos et al, 2005;Katterer et al, 2006). However, the lower depth of the topsoil layer can vary from 15 cm (Bellamy et al, 2005) to 30 cm (Martin et al, 2009). The data used in this study were sampled by horizon, meaning that there was not a uniform sampling depth between points and the number of samples taken at a given location was dependent on soil morphology.…”
Section: Data Preprocessingmentioning
confidence: 99%
See 2 more Smart Citations